Kajian Senyawa Tiramin dalam produk Olahan: Kajian Literatur - Pawestri, Setyaning; Syahbanu, Fathma (Jurnal Teknologi dan Industri Pertanian Indonesia, 2024)
Recently, food safety issues can be affected by several bioactive compounds such as biogenic amines that can be specifically found in fermented foods due to bacterial decarboxylation of some amino acids by fermentation or spoilage bacteria. Tiramin is a biogenic amine produced through decarboxylation of the amino acid tyrosine in animals, plants and microorganisms. Tiramin can cause adverse health effects, such as histamine and tyramine poisoning, histamine and tyraminentolerance, or hypertensive crisis caused by the interaction between tyramine and monoamine oxidase inhibitor drugs. Tiramin is often found in fermented, aged, preserved, and spoiled foods where microbes with decarboxylase enzymes convert the amino acid tyrosine to tyramine. Therefore, information related to rapid and sensitive determination methods for tyramine in various types of food is urgently needed to properly monitor and control the safety of food products. The development of modern technology in food storage (e.g., temperature and pH, packaging) can decrease tyrosine decarboxylase activity and reduce tyramine levels in modern foods. The aim of this article was to review the study of tyramine compounds contained in food products, such as tyramine compounds, issues related to tyramine, the mechanism of action of tyramine in the human body, pathophysiology, clinical significance, pharmacology of tyramine, the toxicity of tyramine, methods commonly used to detect the presence of tyramine compounds, and the methods that can be performed to reduce tyramine levels in food products to tolerable limits according to applicable regulations. This article review was conducted using the narrative literature review method.